PENGARUH KOMPENSASI, KEDISIPLINAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. ANDRE TEKNIK MANDIRI SURABAYA - Asep saefulloh; Roziana Ainul Hidayati; Etika Asia Fahmi (Jurnal Manajerial, 2019)
This study aims to examine the effects of compensation, discipline and work experience on employee performance. The number of samples in this study 44 employees at PT. Andre Teknik Mandiri Surabaya. Data analysis used is multiple linear regression analysis. The results of this study conclude that the results of partial compensation test have an effect on and significant to performance, discipline also have an effect and significant to performance and work experience have an effect on and signifikan to performance.